Successful I CEMACYC and the General Assembly of the REDUMATE - , Red de Educación Matemática de América Central y El Caribe (2014)
Successful 1st Congress on Mathematics Education for Central America and the Caribbean (I CEMACYC) and the General Assembly of the Mathematics Education Network for Central America and the Caribbean (REDUMATE)